Analysis of Social Return On Investment (SROI) To Measure The Social, Environment, And Economics Impact On The National Fattening Sheep Program (Studi At Pesantren Al-Ittifaq) - Khairunnisa Khairunnisa; Ayu Bianti Pribadi; Fajar Sidiq Adi Prabowo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2019)
PT Sarana Jabar Venture (SJV) is the first regional venture capital company in Indonesia, which was established with the aim to foster small entrepreneurs through financing and management guidance. The financing of cooperation implemented on the basis of the principle of mutual strengthening, mutual need and mutual benefit. In addition to financing for small medium enterprises, SJV currently is running a program that is carried by the Medco Foundation IE is a Program of the national Sheep Fattening (Prodombas) and empower the Pesantren to carry the people's economy, one of which is Pesantren Al-Ittifaq. PT Sarana Jabar Ventura viewed from its objective, may be classified as Social Entrepreneur that describes all the economic program that serves the social and mission or mission environment and invested most of the anniversary surplusnya in support of its mission, provide social innovation how to solve social problems by creating breakthrough social problem solving with the advent of Prodombas. So, produce an effect known as social impact as the effects of what organizations are doing or action against social welfare organization. One of the tools for measuring the social impact is by using Social Return on Investment (SROI) the New Economics Foundation (NEF, 2008). This research has the end result of the ratio between the number of comparisons with a benefit that is formed with a given amount of investment, with the result that means 1.05:1 each Rp. 1 invested, yielding the value of social benefits in the form of Rp. 1.05 felt by program participants in Pesantren Al-ittifaq. Because the ratio of 1:1 which is the conditions exceeds successful SROI, then PT Sarana Jabar Ventura as an investor has successfully acted as agents of social reformers because it has given the social impact that bring benefit for participants in Pesantren Al-Ittifaq.